2020
DOI: 10.1002/cssc.202002580
|View full text |Cite
|
Sign up to set email alerts
|

Scalable Photocatalyst Panels for Photoreforming of Plastic, Biomass and Mixed Waste in Flow

Abstract: Solar-driven reforming uses sunlight and a photocatalyst to generate H 2 fuel from waste at ambient temperature and pressure. However, it faces practical scaling challenges such as photocatalyst dispersion and recyclability, competing light absorption by the waste solution, slow reaction rates and low conversion yields. Here, the immobilisation of a noble-metalfree carbon nitride/nickel phosphide (CN x j Ni 2 P) photocatalyst on textured glass is shown to overcome several of these limitations. The 1 cm 2 CN x … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(99 citation statements)
references
References 36 publications
1
89
0
Order By: Relevance
“…Beside the batch reaction, we also conducted studies applying a recently reported flow setup using a photocatalyst panel, 31 which allowed the utilization of the pure, colored PE decomposition solution, as the light absorption losses are minimized in this configuration ( Figure S7 ). The flow setup employed a flow cell with the mounted photocatalyst panel, where the photocatalyst was deposited by dropcasting a catalyst suspension on a frosted glass sheet (25 cm 2 ; Figure S8 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Beside the batch reaction, we also conducted studies applying a recently reported flow setup using a photocatalyst panel, 31 which allowed the utilization of the pure, colored PE decomposition solution, as the light absorption losses are minimized in this configuration ( Figure S7 ). The flow setup employed a flow cell with the mounted photocatalyst panel, where the photocatalyst was deposited by dropcasting a catalyst suspension on a frosted glass sheet (25 cm 2 ; Figure S8 ).…”
Section: Resultsmentioning
confidence: 99%
“…The optimization of the dropcasting process was discussed in our previous study. 31 The reaction solution was pumped through the flow cell, while the photocatalyst sheet was irradiated from the back. Back irradiation of the photocatalyst panel allows light to reach the photocatalyst without being absorbed by the colored reaction solution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To boost the photocatalytic activity, a CN x /Ni 2 P panel instead of NPs as the photocatalyst was constructed by immobilizing the CN x /Ni 2 P material on textured glass, and the purposes of the new configuration were to ease the recycling of the catalyst and obviate the competing light absorption by the matrix. [54] Upscaled panels of 25 cm 2 area of the photocatalyst were employed to transform various waste solutions such as cellulose, PET, and municipal solid waste in flow at ambient temperature and pressure under simulated solar light in 0.5 m KOH solution to generate satisfactory yields of H 2 gas. Moreover, approximately 50 % of the photocatalytic activity was maintained under even milder conditions (seawater, 0.2 sunlight irradiation).…”
Section: Photo-reforming Of Plastic Wastes To Generate Hmentioning
confidence: 99%
“…Furthermore, to overcome practical scaling challenges of traditional powder photocatalyst systems, such as sedimentation, difficult to recycle, and competing light absorption with waste solution, Reisner and co-workers have immobilized the CN x |Ni 2 P photocatalyst on textured glass (Supplementary Figure 4I) (Uekert et al, 2020b). It has been found that the 1 cm 2 square CN x |Ni 2 P panel can photoconvert waste plastic into H 2 and organic molecules with rates comparable to those of photocatalyst slurries, while enable facile photocatalyst recycling.…”
Section: Photocatalytic Plastic Upgrading To Fine Chemicals Integrated With H 2 Productionmentioning
confidence: 99%